Giving increased value to invertebrates conservation through entotourism activity in current and planned ecotourism activity. Tourist attitudes preliminary study in Sabah, Borneo of Malaysia - Ak Mohd Rafiq Ak Matusin; Fiffy Hanisdah Saikim; Norazah Mohd Suki; Mahadi Menakbar M. Dawood (2015)
Tabin Wildlife Resort in Tabin Wildlife Reserve, Lahad Datu, Sabah is a popular tourist spot in Malaysia for being the largest wildlife reserve by mainly focusing on endangered mammals and birds. Thus, in this research, it is proposed to include invertebrates’ information in the current ecotourism activities in Tabin Wildlife Reserve. Implicitly, it could increase a sustainable invertebrates’ conservation. Invertebrates possess large benefits to humankind, namely waste recycling whereby, they cycle the minerals and organic minerals for plants and animals. Thus, this investigation aimed to study the tourists’ perception on including invertebrates’ information in current Tabin Wildlife Resort ecotourism activity. Hence, to collect data from tourists, pre-visit and post-visit questionnaire surveys were adopted as the methodological approach during preliminary entotourism activity. Two different conceptual framework sets (pre-visit and post-visit) were posited in this investigation. The collected data were analysed via Statistical Package for Social Sciences (SPSS) and Analysis of Moment Structure (AMOS) software program by adopting Structural Equation Modelling (SEM). SEM analyses revealed that both pre-visit and post-visit surveys have significant variance towards the ecotourism. This implied a good potential in including invertebrates in ecotourism activities especially in Sabah. The findings of this study are important to contribute to the literature of invertebrates’ species conservation awareness in Sabah, since very limited researches are conducted specifically on entotourism field.